Seismic response of a light rail transit station equipped with braced viscous damper - Azhdar, Amir Fateh; Hejazi, Farzad; Ramanathan, R. A.; Jaafar, Mohd Saleh (Universiti Putra Malaysia Press, 2016)
The use of the Light Rail Transit (LRT) system is currently preferred because LRT is sustainable, improves travel options and facilitates swift mobility in urban areas. Hence, the structural stability and safety of this public transportation system against seismic occurrences are indispensable. Given that these structures cannot be considered conventional frames because of their complex architectural design, focussing meticulously on reliable seismic design codes and structural rehabilitation techniques is vital for the design of the lateral resistance system. One Malaysian LRT station is considered in this study, and the seismic response of this train station when equipped with supplementary viscous damper devices is evaluated. Thus, the LRT station is modelled through finite element simulation. The methods of seismic analysis are limited to linear seismic analyses, namely, response spectrum and time history analyses. Results derived in this study show a significant improvement in structural response when the station is fitted with dampers; approximately 40% reduction in displacement is observed at the top joint of the roof. Furthermore, the lateral base shears decrease by approximately 70%.